The impact of COVID-19 pandemic on nosocomial infections in the cardiac care unit of a non-epidemic hospital in China - Xiang Liao; Wei Wu; Lijuan Zhang; Zheng Zhang; Chengrong Zheng; Xincheng Qiu; Chao Xin; Zhitao Jin (Frontiers in Medicine)
BackgroundCOVID-19 is generally believed to increase the risk of nosocomial infections, however, there is a gap in relevant researches on critically ill patients in cardiac care units (CCU).MethodThis cross-sectional research was conducted in a tertiary-level non-epidemic hospital of Beijing, capital of China. The nosocomial infection rates of CCU were assessed prior to and during the of COVID-19 outbreak.ResultsDuring the COVID-19 pandemic, the overall incidence of nosocomial infections decreased by 20.6-percent compared with the pre - pandemic period. Specifically, the total nosocomial infection rate during the COVID-19 pandemic (p = 0.04) decreased by 20.6%. Among various types of CCU-acquired nosocomial infections, the rates of pneumonia, urinary tract infection (UTI), bloodstream infection (BSI), gastrointestinal infection, and skin infection decreased by ranges from 4.7 to 100% during the COVID-19 pandemic. Meanwhile, a 1.5-percent increase in ventilator-associated events (VAEs) was observed during the COVID-19 pandemic.ConclusionDuring the COVID-19 pandemic, stricter implementation of infection control protocols appears to reduce nosocomial infections in CCU.